POLICY DIRECTIONS FLOOD DISASTER MITIGATION IN KAMPAR REGENCY, RIAU PROVINCE - Etika Sihaini; Dedi Hermon (Universitas Sebelas Maret (UNS), 2025)
There have been many studies on flood disaster mitigation policy directions, but they have not been widely developed in Indonesia as a tropical country with a unique rainfall pattern. This is an indicator used to assess the level of flood disaster vulnerability. Exceptionally high rainfall intensity always causes flood disaster problems in Kampar Regency. This study aims to 1) formulate the level of flood vulnerability in Kampar Regency, Riau Province, 2) analyse the characteristics of land in Kampar Regency, Riau Province, 3) formulate flood disaster mitigation policy directions by the Kampar Regency Government, Riau Province. The method used in this study is quantitative, and it is a survey and spatial analysis. This study was conducted in Kampar Regency, Riau Province. Furthermore, in processing flood disaster mitigation policy directions, the AHP (Analytical Hierarchy Process) method is used to formulate appropriate priority directions to mitigate flood disasters. Based on the results of the study, the level of flood disaster vulnerability with analysis using the GFI method, there are four flood vulnerability zones in Kampar Regency, namely: a high flood vulnerability zone covering an area of 88,658.36 ha, a moderate flood vulnerability zone covering an area of 142,821 ha, a low flood vulnerability zone covering an area of 86,357.23 ha and a flood-free zone covering an area of 715,850.97 ha. Furthermore, based on data processing through expert choice software, the direction of flood disaster mitigation policies is determined to have 9 alternatives. With these alternatives, it is hoped that they can be formulated to reduce the risk of flood disasters in Kampar Regency.